Artificial Minds: Analyzing AI’s Role in Science Fiction Narratives - Gowtham S.,; Dr. P. N. Gunanidhi, (International Journal of Scientific Research in Science and Technology, 2024)
This paper explores the intersection of Artificial intelligence (AI) and its analysis in the domain of Science Fiction while using AI both as content and a methodology. The analysis of AI characters, narratives, and motifs in science fiction is used in the study to show how far literary inventions of Artificial Intelligence correspond to and question the human understanding of independence, morality, and personality. It focuses on how it is possible to use machine learning to detect the recurrences of tropes, the characters’ types, and AI themes in the history of science fiction literature as well as the attitudes of culture to technology. Besides, the study concerns AI as an author and a critic, which extends limits to creativity and authorship. In the same way, it looks at the interactions between AI and man, and the moral issues they pose in the science fiction lens, to give an insight on what society fears and looks forward to from advancement in technology. This approach focuses on how artificial intelligence and literary analysis improve our understanding of science fiction and forges literature as a tool for exploring the ethical, psychological, and cultural implications of AI.
Keywords: Artificial Intelligence; Science Fiction; Literary Analysis; Machine Learning; Ethical Dilemmas; AI-Human Relationships; AI Critic